Enhancing Student Interest in Islamic Education Through Educational Game-Based Learning with Coastal Local Wisdom - Nurjanah, Siti; Shofianti, Sherly; Sari, Ferlina; Rohman, M. Mukhibbur (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This research aims to increase students' interest in learning through Islamic Religious Education (PAI) learning based on educational games with local coastal wisdom in class XI of SMK NU Palang. Interest in learning is an individual's inner driving force in learning activities to increase knowledge, skills and experience. The research method used is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, action, observation and reflection stages. The research subjects were 25 students from class XI AKL. The data collection instruments were in the form of a learning interest questionnaire and observation sheets. The research results showed a significant increase in students' interest in learning, with a completion percentage reaching 70% in cycle II, exceeding the initial target of 46%. The application of educational game-based PAI learning with local coastal wisdom through the creation of Mind Maps and the Problem-Based Learning (PBL) approach has proven effective in increasing students' interest in learning. This research contributes to the development of PAI learning methods that are more structured and applicable, and encourage students to have a high interest in learning.